Earlyonset twin–twin transfusion syndrome: case series and systematic review - MylreaFoley,B; Shaw,CJ; Harikumar,N; Legg,S; Meher,S; Lees,CC (Australasian Journal of Ultrasound in Medicine, 2019)
IntroductionData on the outcomes of earlyonset twin–twin transfusion syndrome (TTTS), diagnosed before 18 weeks gestational age (GA), are sparse. We aimed to review the diagnosis, management and outcomes of earlyonset TTTS.Material and methodsPregnancy records at a single referral unit 20106 were reviewed. In earlyonset TTTS cases, data for pregnancy characteristics, interventions and outcomes were collected. PubMed and Scopus databases were searched for studies including pregnant women with earlyonset TTTS. The primary outcome measure was livebirths.ResultsCase series: 58 cases of earlyonset TTTS 20106, with full outcome data in 44. Diagnostic criteria were variable. Median GA at intervention was 17+4 (range 15+028+1); 67% of patients had laser therapy (39/58). Overall survival: 60% (53/88). At least one livebirth: 86% (38/44), Two livebirths: 34% (15/44); No survivors: 14% (6/44). GA at delivery was 32+1.5 (range 16+237+4). Systematic review: 16 studies included (n = 171 pregnancies). Diagnostic criteria varied widely: 79% of studies used Quintero staging. Most offered laser (89%) at median 17+0 weeks (range 16+021+6). GA at delivery was 23+039+5 weeks. Overall survival: 69% (129/186). At least one livebirth: 74% (127/171). Two livebirths: 59% (55/93). No survivors: 26% (44/171).ConclusionsIn comparison with the commonly accepted overall survival for TTTS treated after 18 weeks of 60–90%, outcomes in earlyonset TTTS were at the lower bound of this range. Gestational age at intervention is similar to that of later onset TTTS, indicating a lack of therapeutic options when a diagnosis is made before 18 weeks.